Contemplation by Design: Leveraging the “Power of the Pause” on a Large University Campus Through Built and Social Environments - Chrisinger, Benjamin W.; Rich, Tia (Frontiers in Public Health, 2020)
College and university campuses have long been designed as embodied places of societal values and aspirations, reflecting both academic traditions and heritages alongside social and scientific change and innovation. More pragmatically, these spaces share some commonalities with other living and working environments, and must adapt to changing technological and social norms. Since the 1970s, workplace adaptations included employer-sponsored health promotion programs and facilities. While campus environments such as fitness centers and dining halls have been incorporated into health promotion initiatives, other aspects of human well-being have been neglected. In this paper, we describe an initiative, Contemplation By Design, to incorporate contemplation and mindfulness into the daily lives of all members of the Case University community, including students, faculty, staff, and their families, as well as alumni and retirees who live close by. This case study highlights ways that physical planning and programmatic initiatives for contemplative practices have been integrated to deliver generalizable, community-based well-being resources that can be emulated in diverse settings throughout the Case University campuses, including the main campus and local satellite campuses. Based on experience drawn from Contemplation By Design, practical recommendations for designing contemplative practice spaces and programs are offered.